The affective and participatory responses of students paired according to proficiency levels in dyadic exchanges - Gregersen, Tammy (Lenguas Modernas, 2017)
Interaction and the affective response that this generates in the language learner affects the acquisition process. The purpose of this study was to discover whether a student's language proficiency level was a contributing fáctor to the variability found in the frequency of participation in dyadic exchanqes and whether students experience different affective reactions when paired with a partner at a higher, lower, or similar language level. Sixteen university students of high, intermediate and low proficiency levels were paired homogeneously and heterogenously and were asked to participate in information exchange activities. The frequency of their interaction and their affective responses were measured. The results of this study confirm that affective responses in language learners change depending on the proficiency level of the person they are partnered with in dyadic exchanges. Furthermore, the proficiency level of a student is a contributing factor in the variability of the frequency of participation in dyadic exchanges between foreign language studen ts.